University proceedings. Volga region. Social sciences - D.V. Elistratov (Известия высших учебных заведений. Поволжский регион: Общественные науки)
Background. The issues of improving the theory and practice of tactical and spe-cial training of employees of internal affairs bodies (IAB) in modern conditions, in which fundamentally new threats arise - attacks on the internal affairs bodies' own facilities by army armed groups, including sabotage ones, have been updated. Therefore, the aim of the study was to find new approaches to organizing and conducting classes on tactical and spe-cial training of the personnel of the Internal Affairs Directorate, including abandoning the principle of causing the least harm to the attacker, in the event of an armed attack on a In-ternal Affairs Directorate facility, taking into account, within the framework of tactical and special training, certain training elements used in the Armed Forces. Materials and meth-ods. The study was conducted by analyzing the norms of Russian legislation and the works of domestic legal scholars. Regulatory legal acts, the provisions of which should be taken into account in the framework of tactical and special training, were considered. Results. Tactical and special training of police officers in modern conditions can be criticized from the point of view of the lack of deep differentiation depending on the employee’s previous training. When determining options and models of behavior, police officers must take into account the requirements of the law and not allow the permissible limits of violent influ-ence on the offender to be exceeded. Conclusions. When armed army units encroach on objects of the Internal Affairs Directorate, the principle of causing minimal harm to the encroacher is extremely inappropriate and erroneous, and its application will only lead to the death of the Internal Affairs Directorate employees and the seizure of the object. It would be advisable to introduce into the practice of tactical and special training the meth-ods that are used in training army units.